“We’re the Town’s Help Desk:” Social Work Creep in America’s Last Public Space - Furukawa, Diana; Scott, Olivia; Treat, Ben (Maine Policy Review, 2024)
Based on interviews with public library staff from across the state, the authors find that Maine library workers are increasingly serving as frontline responders for people with unmet basic needs and addressing intensifying behavioral issues. This results in “social work creep”, in which libraries inadvertently take on roles traditionally filled by social service agencies. Libraries are responding by building partnerships with social services agencies, reassessing library policies and enforcement methods, and seeking training in de-escalation and overdose response, but at a significant cost to staff wellbeing and core library services. The authors recommend that policymakers focus on systemic solutions including housing initiatives and local, direct support for people in crisis.